Redefining the Role of Mobile Phones in Accounting Education: Exploring Students' Perspectives - Khulood khalifa almusalhi; Huria Saleem alabri; Mohammed Muneerali Thottoli (Profesional Muda Cendekia Publishing, 2023)
Purpose: Equitable access, choosing suitable apps, eliminating distractions, assuring compatibility, and providing efficient teacher training for successful integration challenges with using mobile phones as teaching aids in accounting education. Hence the current research examines students' perceptions of using smartphones in accounting education.Design/ Methodology/ Approach: Quantitative data was gathered from 101 students in accounting programs at universities in Oman. The data is then analyzed using the Partial Least Square Structural Equation Modelling (PLS-SEM) technique. Findings: Both hypotheses are supported wherein students' Perception of the use of mobile phones as a learning tool with accounting education shows p < 0. 001, t=4.896, and university/college policy on using mobile phones with accounting education show p < 0. 001, t=4.020. This result indicates that Students’ Perceptions of (using mobile phones as a learning tool and university/college policy on using mobile phones) significantly impact accounting education.